Send them tractors not tanks - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Berkeley:::University place::::::::::::
Image of a tractor and a tank. The words "SEND THEM TRACTORS NOT TANKS" is written between the two images.